TINJAUAN TEOLOGIS TERHADAP PENDEKATAN EVIDENSIALIST DALAM PERSPEKTIF REFORMED THEOLOGY - Made Nopen Supriadi (Sekolah Tinggi Teologi Arastamar Bengkulu, 2019)
In the context of apolegetics known as the presupposition approach and evidentialist approach. However, many debates have led to disputes because of the overwhelming evidence that supports each other. Is it true that the defense of faith and the basis of faith always rest on evidence. Through this paper, we will explore a little about Reformed presuppositions as a theological review of the evidentialist approach.